Implementasi Program Gerdu Kempling di Kelurahan Palebon Kecamatan Pedurungan Kota Semarang - Ayu, Astrid Ratri Sekar; Nurcahyanto, Herbasuki; Marom, Aufarul (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2014)
Poverty is a complex problem in Indonesia especially in central cities. Semarang is one of central cities which is facing poverty and trying to take an effort through Gerdu Kempling program. Gerdu Kempling program is a partnership program between government, citizen, and private in health, economy, education, infrastructure, and environment sector which manage to decrease poverty.The purpose of this research is knowing the implementation of Gerdu Kempling program at Palebon District and knowing factors which influence the succeess of it. This research is using the efectivity of policy implementation theory to analyze the success of Â Gerdu Kempling program implementation at Palebon District and also using the policy implementation model of Merilee S. Grindle to analyze the factors which influence the succeess of it.The result of this research indicates the implementation of Gerdu Kempling Program at Palebon District has fullfiled the criteria of policy implementation efectivity. The factors which influence the success of policy implementation consist of content of policy, context of policy, and output, result, and impact of policy. The content of Gerdu Kempling program has matched with the target needs and the context of policy has supported the policy implementation. The output, result, and impact of policy indicates that the implementation of Gerdu Kempling program at Palebon District has increased the number of prosperity for Palebon citizens.Â